(3eUHGM GdCfGe aj TQM TQGFY GdESdGe cJGH GdMLQs - (3GdfLaj, , GdHOjQj, GdHOjQj, LYaQ Hf CMeO Hf Sja, J (B1369(3g` (B1950(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3bhdg cJGH GdMLQ, GdMLQ gh GdefY hGdeMLhQ TQkYG ge GdeefhY ef GdJUQa aj eGdg hGdfXQ aj gPG GdHGH jSJOYj aUdjf, GdChd aj ehLHGJg hgj SJI(B: (3GdUZQ hGdLfhfs
(3BNQgG (B:s
(3BNQgG(B: (3hGdHMK YfgG djS hXjaI Gdabjg hdPG NdJ Yf GdfUhU hGYQVfG Yf GdGWfGH HPcQgG aEf KHfJ GdJfHjg Ydi Pdc fMjdc HHYV cJH Gdbhe cGdeHShW (B.. (3hZjQgeG aEf ajg eG JQjO(B. (3hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 121s
(3GdPQjYI, L (B21: 68s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis